Modeling of a library communication - S. A. Ezova (Библиосфера, 2012)
The elements of a communication model as a process are disclosed, special attention is paid to the transfer of the content of a message, conditioned by communication functions and library functions. An attempt is made to model library communication, basing on significant logical basis.